P040 Reducing the late diagnosis of HIV – where are we? An experience from a county perspective. (30th June 2016) - Healy, Richard; Sanmani, Leela; Wallace, Sophie; Jordan, Catherine
Abstract : Background/Introduction: HIV is a treatable medical condition, and death rates are similar to other long term conditions if the patient is diagnosed early enough for anti-retroviral therapy to have any meaningful effect and if the patient is adherent to their antiretroviral therapy. A late diagnosis is defined as a new HIV diagnosis with a CD4 count of <350 cells/mm 3, or an AIDS-defining illness. Aim(s)/objectives: Identify the numbers of late HIV diagnoses made over a five year period in a county with low prevalence. Educate hospital junior doctors & GPs about the consequences of a late diagnosis of and when to test for HIV. Methods: The numbers of positive HIV tests were obtained, plus the patients' CD4 count at the point of a positive HIV test over a five year period. Patients were included or excluded based on the following criteria. Included : over 18; new diagnosis of HIV within secondary care; CD4 count <350/AIDS defining illness. Excluded : antenatal testing, occupational health test; GP testing. Results: Fourteen patients identified. 12/14 were heterosexual white British males 11 of whom were diagnosed in hospital and mostly admitted under the acute medics. CD4 counts ranged from 0.01 to 475 with a mean count of 224 cells/mm 3 . Discussion/conclusion: As a direct result of the talks delivered presenting the findings of the project, at the time of writing, two major changes in practice have occurred and there is closer collaboration between the hospital physicians, microbiology lab and the HIV consultants. A poster has been designed and is now found in numerous hospital sites.